Digital Transformation in the Records Management of a Private Higher Education Institution in the Philippines - Maria Andrea A Wagan; Jesus Briones; Flormando P Baldovino; Rey Fernan G Refozar (Research Synergy Foundation, 2025)
Digital transformation is revolutionizing record management and igniting a bold new era of unparalleled efficiency, enhanced security, and seamless accessibility. This study assessed the implementation of digital record management across three dimensions: efficiency gains; strengthening accuracy; and best practices and identified the challenges organizations face in achieving these goals. This descriptive-quantitative study used a researcher-structured questionnaire to collect data from 56 randomly sampled employees of a private higher education institution (HEI) in the Philippines. The data were analyzed using frequency, percentage, weighted mean, and Spearman's rank correlation analysis. The report highlights best practices in digital record management and delves deeper into data accuracy and security enhancements. The findings also demonstrate that the HEI is working hard to implement best practices in digital record management, including establishing a well-defined plan for the transition from paper to digital records. Implementation obstacles such as data loss and compatibility problems are discussed, and it is revealed that there is no meaningful connection between these challenges and the implementation of digital records management. A proposed strategy roadmap is recommended by the researchers to enhance digital record management in the subject HEI. This study on digital transformation in the records management of a private HEI in the Philippines has the potential to drive significant improvements in the institution’s operations, enhance its reputation and contribute to the broader goals of HEIs in the country.